La vie des réfugiés volontaires de l’accident nucléaire - Takezawa, Shōichirō (Ebisu : etudes japonaises, 2021)
The accident at the Fukushima Daiichi Nuclear Power Station resulted in 170,000 evacuees, and 10 years on their number still exceeds 40,000. The Japanese government set the standards of compensation that it ordered TEPCO to pay evacuees. However, many evacuees are dissatisfied with the compensation amount and by the absence of a government apology, with some 15,000 people filing 28 lawsuits against TEPCO and the government. Based on the statements submitted to the court and on our questionnaires, this paper seeks to establish a “life document” of 171 evacuees from 54 households who filed a complaint with the Kyoto District Court.